Campaigning for social justice: increasing public access to professional social workers - Wayne, Raymie Harvard; Limone, Christine; Karp, Stephen A (Reflections: Narratives of Professional Helping, 2017)
Citation Key Alias: lens.org/101-877-855-921-650
Keywords: dept.swk; peer-reviewed; ⛔ No DOI found

A "Just Sense of Well-Being": Social Work's Unifying Purpose in Action. - Keenan, Elizabeth King; Limone, Christine; Sandoval, Silvia L (Social work, 2017)
For over a century the social work profession has had a dual purpose, to promote both human well-being and social justice, but we have not found research that explores how social workers understand and work toward both purposes across multiple practice roles and settings. Authors of this article conducted qualitative research to examine how 18 social workers in various roles and settings understand and implement both purposes in their practice. Instead of a dual purpose, participants described a unifying purpose: a "just sense of well-being" that transcends role and setting. Valuing the dignity and worth of all human beings frames and fuels their work toward a just sense of well-being through three interactive themes: challenging injustice on every level; constructing justice through relationship and resource organizing; and constructing justice through the creation of accepting environments where professionals, clients, and community members can reflect and question, and change mind-sets and actions. Participants provided an array of possibilities for action with clients, professionals, and public leaders within organizations and communities. The implication here is that social workers are charged to reinvigorate purpose and values back into practice with value-based assessment thinking that frames possibilities for action across methods and settings. Copyright © 2016 National Association of Social Workers.
5 citations (Crossref) [2023-10-31] Place: United States Keenan, Elizabeth King. Department of Social Work, School of Health and Human Services, Southern Connecticut State University, New Haven, USA. Limone, Christine. Department of Social Work, School of Health and Human Services, Southern Connecticut State University, New Haven, USA. Sandoval, Silvia L. School for Social Work, Smith College, Northampton, MA, USA.
Keywords: *Professional Role/px [Psychology]; *Social Justice/px [Psychology]; *Social Work/mt [Methods]; *Social Workers/px [Psychology]; Adult; Female; Humans; Male; Middle Aged; Professional Role; Qualitative Research; Social Justice; Social Work; Social Workers; Social justice; Social work practice; Values; Well-being; adult; dept.swk; dual purpose; female; human; human dignity; human experiment; leadership; male; middle aged; occupation; organization; procedures; professional standard; psychology; qualitative research; social justice; social work; social work practice; social worker; thinking; wellbeing